PENGARUH LEVERAGE TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIATAHUN 2018-2020 - Puka, Yosefina Lodan; Amtiran, Paulina Yuritha; Ndoen, Wehelmina M (GLORY Jurnal Ekonomi dan Ilmu Sosial, 2022)
This study aims to see the effect of Leverage as measured by the Debt to Equity Ratio and Debt to Asset Ratio on Profitability. The population in this study were 30 food and beverage companies listed on the Indonesia Stock Exchange and the samples used in this study were 5 food and beverage companies listed on the Indonesia Stock Exchange in 2018-2020. This study uses quantitative methods, namely by testing the hypothesis. In this study, the type of data used is panel data. Panel data is data that has two characteristics that are combined in a data between time series data and cross section data. Hypothesis testing is done by using panel data regression using Eviews 9 software. The results of the analysis through hypothesis testing, simultaneously Debt to Equity Ratio and Debt to Asset Ratio have a positive and significant effect on Profitability. Partially Debt To Equity Ratio has a negative and significant effect on profitability, Debt To Asset Ratio has a positive and significant effect on profitability. Key words: leverage, Profitability, DER, DAR, ROA